A tutela jurídica do capital intelectual das sociedades empresárias - Abdallah, Ana Claudia Karam (Universidade de São Paulo, 2009)
Na atual era pós-industrial, o conhecimento passa a ser o principal fator de produção da economia. De fato, ele confere à empresa seu maior diferencial competitivo no mercado globalizado: a inovação, ou seja, a capacidade de, continuamente, gerar novos produtos, processos e serviços ou aperfeiçoar os existentes. A organização da empresa em sociedade empresária possibilita a criação de conhecimento coletivo oriundo do trabalho profissional dos seus sócios, administradores e empregados, fato que originou a expressão capital intelectual, cunhada no âmbito econômico para designar o patrimônio empresarial de natureza intangível resultante de contribuições intelectuais. Como o Direito é precedido da evolução das sociedades e da Economia, nota-se a importância de sempre se buscarem soluções jurídicas às novas realidades socioeconômicas que surgem ao longo da história. Diante disso, a análise da natureza jurídica e das formas de tutela do capital intelectual torna-se imperativa para a identificação e apropriação privada desse patrimônio pela sociedade empresária, seja por meio do exercício de direitos de exclusivo, seja pela implementação de mecanismos de governança capazes de assegurar a diferenciação da atividade empresarial no mercado e a necessária coibição de práticas de concorrência desleal. In the current post-industrial age, knowledge becomes the main production factor of the economy. Indeed, it provides the company with its main competitive advantage in the globalized market: the innovation, that is, the capacity of continuously generating new products, processes and services or enhance the existing ones. The companys organization as business company allows the creation of collective knowledge arising from the professional work of its partners, officers and employees, which fact originated the term intellectual capital, created in the economic scope to designate the corporate equity of intangible nature resulting from intellectual contributions. As the Law came after the evolution of the companies and of the Economics, it is noted the importance of the constant search for legal solutions, the new socioeconomic realities that appear along the history. In view of that, the analysis of the legal nature and of the forms of protection of the intellectual capital becomes critical for the identification and private appropriation of such equity by the business company, either by means of the exercising of exclusive rights or by the implementation of governance mechanisms capable of ensuring the differentiation of the corporate activity in the market and the required restraining of unfair competition practices.
Keywords: Capital social; Concorrência desleal; Direito empresarial; Estabelecimento comercial; Intangible; Intellectual capital; Intellectual property; Propriedade intelectual; Sociedade comercial; Unfair competition

O Estado como acionista controlador - Pinto Junior, Mario Engler (Universidade de São Paulo, 2009)
O presente trabalho acadêmico procura construir um referencial teórico baseado no ordenamento jurídico brasileiro para definir o papel da empresa estatal no mundo contemporâneo. Trata-se do ponto de partida para compreender a atuação do Estado como acionista controlador e as regras de convivência com acionistas privados em posição minoritária e com outros grupos de interesse afetados pela atividade empresarial. A abordagem do tema apóia-se na idéia central de que toda empresa estatal está investida de uma missão pública, explícita ou implicitamente incorporada no objeto social, que varia conforme a natureza da atividade exercida e está sujeita a adaptações ao longo do tempo. A missão pública coexiste com a finalidade lucrativa inerente ao modelo de companhia e serve para condicionar a ação do Estado enquanto acionista controlador e dos administradores, dando conteúdo a seus deveres fiduciários. This dissertation aims at establishing a theoretical framework according to Brazilian law to identify the role of state-owned enterprise in contemporary world. This is the first step to understand what the governments behavior should be as a controlling shareholder and the legal rules applied to its relationship with equity investors and others stakeholders. The approach is based on the assumption that every state-owned enterprise has a public mission implicitly or explicitly included in its bylaws objectives. The public mission varies according to the nature of the business and should be redefined from time to time to keep adherence to the external environment. The public mission coexists with the companys profit scope and guides the States actions, as well as those of directors and officers. For that reason the public mission is embedded in their fiduciary duties.
Keywords: Acionista majoritário; Actionnaire majoritaire; Board of directors; Conselho de administração; Controle acionário; Controlling shareholder; Corporate governance; Empresas públicas; Entreprise publique commerciale; Etat; Fiduciary duties; Governança corporativa; Mixed capital corporation; Public interest; Sociedade de economia mista; State-owned enterprise

Les Incidences de la diversification des valeurs mobilières sur le droit de vote dans les sociétés par actions - Traoré, Assétou (Université d'Auvergne - Clermont-Ferrand I, 2009)
La diversification des valeurs mobilières a entraîné une dissociation des attributs de l'action. Elle remet en cause certains principes fondamentaux du droit des sociétés, au cœur desquels la question du droit de vote. La suppression du droit de vote entraine des interrogations. Peut-il être considéré comme inhérent à l'action ? Est-il aujourd'hui une condition nécessaire à la qualification d'associé ? Quelles alternatives trouver alors au droit de vote ? Parce qu'elle touche à l'équilibre capital- pouvoir fondant les sociétés par actions, elle remet en cause la cohérence au sein de la société. Parler des incidences de la diversification des valeurs mobilières sur le droit de vote nous conduit à une analyse renouvelée des bases de la société. Le droit de vote n'est pas une condition de l'existence de l'actionnaire mais plutôt un moyen de défendre ses droits pécuniaires. Si le droit de vote ne peut plus être considéré comme essentiel à l'action, ne doit-on pas lui substituer le droit de participer. Par ailleurs, la diversification des valeurs mobilières révèle le fossé grandissant entre les sociétés fermées et les sociétés ouvertes, le droit de vote y perd son importance. Le constat est celui d'une affirmation des spécificités existant entre ces deux types de sociétés. Mais au-delà de ces mutations, il existe une cohérence profonde. Aussi, la reconnaissance d'un principe de droit commun pour les sociétés par actions avec une prise en compte des spécificités par le droit des marchés financiers apparaît à notre sens la situation la plus appropriée.
Keywords: Actionnaires; Droit de vote; France; Sociétés de capitaux; Valeurs mobilières

A função social da empresa e a composição de interesses na sociedade limitada - Matias, João Luis Nogueira (Universidade de São Paulo, 2009)
Através do presente trabalho, demonstra-se que a função social da empresa é o fundamento e a justificativa para o reconhecimento e a proteção de interesses alheios aos dos sócios na sociedade limitada. Nos três primeiros capítulos, o objetivo é apontar qual o fundamento teórico da funcionalização do direito de propriedade, quais corolários dela decorrem e qual a sua importância para o exercício da empresa. Defende-se que a função social da propriedade é imperativo decorrente da ordem jurídica do mercado, moldada principalmente pelo princípio da solidariedade social. Por sua vez, a função social da empresa é corolário da função social da propriedade. Sustenta-se que a funcionalização do exercício da empresa repercute no exercício da atividade empresarial, acarretando obrigações positivas e negativas aos sócios majoritários (controladores) e administradores das sociedades empresárias, assim como incide sobre o exercício do direito de propriedade de parcelas do capital, do que decorrem obrigações atinentes aos sócios. A partir do capítulo quarto, objetiva-se sistematizar a composição de interesses na sociedade limitada, em abordagem que inclui tanto os conflitos que envolvem os sócios entre si, como os que os vinculam a terceiros, como a própria sociedade, os credores, os empregados, etc. No primeiro aspecto, versa-se sobre: deliberações sociais; o direito de recesso como forma de resolução de conflitos entre os sócios; a dissolução parcial como instrumento para assegurar a liberdade de não permanecer associado; as restrições ao exercício abusivo da administração; a transparência como instrumento de preservação dos interesses dos minoritários; o direito de participação nos lucros e no acervo social em caso de dissolução e liquidação da sociedade; o direito à manutenção da mesma proporção no capital social e o acordo de quotista como instrumento de composição de interesses. No segundo, sobre o conflito de interesses entre a sociedade e o sócio, em razão do exercício do direito de voto; a exclusão dos sócios nas modalidades de resolução da sociedade em relação ao sócio minoritário, da exclusão do sócio majoritário e do sócio remisso; aspectos da composição do capital social; os efeitos externos da sociedade, em abordagem que apreciará as conseqüências da autonomia patrimonial, a responsabilidade dos sócios e administradores e a desconsideração da personalidade jurídica; aspectos da proteção dos interesses dos empregados e da preservação do meio ambiente. A partir da análise doutrinária e jurisprudencial, demonstra-se como o princípio da função social da empresa é importante para a composição de interesses na sociedade limitada.
Keywords: Atividade comercial; Capital social; Conflict of interests; Conflit d'intérêts; Direito de recesso; Direito empresarial; Firm property; Firm social function; Fonction sociale de l'entreprise; Private limited partnership; Property social function; RSE; Resumo em inglês; Sociedade comercial; Sociedade por cotas de responsabilidade limitada; Société Anonyme

Os limites da intervenção judicial na administração das sociedades por ações - Pantano, Tania (Universidade de São Paulo, 2009)
A legislação aplicável às sociedades por ações utiliza conceitos e normas abertas que devem ser interpretadas com base nos princípios que regem as sociedades por ações, considerando, nessa análise, as características específicas da companhia na qual surgiu a controvérsia e as situações que integram e esclarecem a situação controversa levada a conhecimento do Judiciário. A liberdade dos empresários, na condução de suas atividades, tem fundamento no sistema econômico Brasileiro, conforme princípios da Constituição Federal. No entanto, os interesses sociais protegidos pela Constituição Federal exigem que as empresas, especialmente as sociedades por ações, que agregam características institucionais, estabeleçam limites para a condução das atividades das companhias. Da mesma forma, a criação de um ente autônomo e dotado de patrimônio próprio, cria uma separação entre o poder de controle e administração dos bens, direitos e obrigações que integram esse patrimônio e os acionistas que contribuíram inicialmente para sua constituição, motivo pelo qual a condução dos negócios empresariais deve sempre buscar atingir os interesses da companhia e os agentes necessários para realização dessas atividades têm deveres e responsabilidades com os demais acionistas e terceiros afetados pela existência da companhia. Nesse contexto, a atuação do Judiciário se restringe a verificar a ocorrência de atos ilegais de gestão. O Judiciário, no sistema jurídico brasileiro, não podendo interferir no mérito das deliberações, sob pena de infringir o princípio da livre iniciativa e do exercício do poder de controle, que estruturam o sistema legal que regula as sociedades por ações. A responsabilidade dos administradores e controladores que agem de boa-fé nos atos regulares de gestão deve ser preservada em face dos resultados da companhia e os interesses dos demais sócios.
Keywords: Acionista majoritário; Acionista minoritário; Actionnaire majoritaire; Actionnaire minoritaire; Administration; Assembleia geral; Assemblée générale; Commercial law corporate; Corporations; Intervention judiciaire; Intervention judicial; Management; Sociedade anônima (administração); Sociedade comercial; Sociedade por ações (administração); Société par actions

Anonim şirketlerin ehliyeti (özellikle ultra vires doktrini ile sınırlandırılması) - Serder, Selen (Ankara Üniversitesi, 2009)
Türk Ticaret Kanunu'nda, ultra vires doktrininin etkisiyle, ticaret şirketlerinin ehliyetlerinin işletme konusuyla sınırlandırılması ölçütüne yer verilmiştir. Buna göre TTK.'nun 137. maddesinde ticaret şirketlerinin ehliyetinin işletme konusu çevresiyle sınırlı olduğu kabul edilmiştir. Anonim şirketlerin ehliyeti de TTK. m. 137 kapsamında işletme konusu çevresiyle sınırlandırılmıştır.İşletme konusu, ana sözleşmede yer alan ve şirketin faaliyet göstereceği iş alanlarını somut olarak ortaya koyan bir kavramdır. Sınırlı ehliyet ilkesinin sakıncalarını gidermek amacıyla işletme konusu kavramını geniş yorumlamak ve işletme konusu kapsamındaki faaliyetleri kolaylaştırmak adına yapılan işlem ve faaliyetleri işletme konusundan saymak gerekmektedir.Anonim şirketlerin ehliyetlerinin kapsam ve sınırları, anonim şirket temsilcilerinin yetkilerinin kapsam ve sınırlarını belirlemesi bakımından da önem taşımaktadır. Anonim şirketin ehliyetinin ve buna bağlı olarak temsilcilerinin yetkilerinin kapsam ve sınırlarının belirlenmesi, anonim şirket ortaklarının, alacaklılarının ve kamu menfaatinin korunması amacına da hizmet etmektedir.Ticaret şirketlerinin ve buna bağlı olarak anonim şirketlerin ehliyet dışı işlemleri, öğretide yer alan baskın görüşe göre yok hükmündedir. Ehliyet dışı yapılan işlemin yok hükmünde kabul edilmesi, bu işlemin hiç doğmadığı ve sonradan onay vermekle bu işleme geçerlilik kazandırılamayacağı anlamındadır.Ticaret şirketlerinin ve dolayısıyla anonim şirketlerin ehliyetinin işletme konusu çevresi ile sınırlandırılması ultra vires doktrini olarak ifade edilmektedir. Ultra vires doktrini İngiliz hukuku kaynaklı olup, şirketler hukuku bakımından şirketlerin hukuki ehliyetinin ana sözleşmelerinde yazılı olan konularıyla sınırlandırılması temeline dayanmaktadır. Günümüzde ultra vires doktrini terk edilmiştir. Nitekim Türk Ticaret Kanunu Tasarısı'nın ticaret şirketlerinin ehliyetini düzenleyen 125. maddesinde ultra vires doktrininin yansıması olan işletme konusu çevresiyle sınırlı ehliyet ilkesine yer verilmemiş olup ultra vires doktrininin yarattığı sakıncaları önlemek adına olumlu bir adım atılmıştır. The rule of limited capacity of companies in the frame of the objects clause, was given a place in the Turkish Commercial Code with effect of ultra vires doctrine. According to this, Article 137 of the Turkish Commercial Code stipulates that capacity of companies are limited in frame of the objects clause of the companies. Capacity of incorporated companies are also limited in frame of the objects clause according to Article 137 of the Turkish Commercial Code.Objects clause is a concept which takes place in the memorandum and which shows scope of the company. In order to remove inconveniences of principle of limited capacity, the transactions and activities made for widely interpreting the concept of objects clause and facilitating the activities in the cover of objects clause, are assumed in the frame of objects clause.Contents and limits of capacity of incorporated companies are significant with regard to defining contents and limits of power of directors of incorporated companies. Defining contents and limits of capacity of incorporated companies and whereupon defining content and limits of power of directors also serve the purpose of protecting share holders and creditors of incorporated companies and public interest Companies? transactions and whereupon incorporated companies? transactions, which are out of capacity are nul and void according to the dominant idea in the doctrine. Assuming the transactions that exceed the capacity of company as nul and void means that this transactions were never made and that further approving such transaction would not make it valid. Limited capacity of companies and whereupon of incorporated companies in frame of objects clause is called ultra vires doctrine. Ultra vires doctrine is of English Law origin and based on the limitation of capacity of the companies by the objects clause of the memorandum, with regard to the law of companies. Today, ultra vires doctrine is relinquished. As a matter of fact, Article 125 of the Scheme of Turkish Commercial Code regulating capacity of the companies did not give place the limited capacity principle which is a reflection of the ultra vires doctrine and took an important step in order to avoid the drawbacks of ultra vires doctrine.
Keywords: Anonim ortaklıklar; Capacity; Commercial law; Ehliyet; Incorporated companies; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Ultra-vires

Destinação dos elementos intangíveis do estabelecimento empresarial e do aviamento na extinção parcial do vínculo societário - Chinalia, Olavo Zago (Universidade de São Paulo, 2008)
O conhecimento constitui bem jurídico, passível de tutela tanto sob a ótica da criação - por meio dos direitos de propriedade intelectual - quanto sob a ótica da sua utilidade econômica - juntamente com os demais elementos intangíveis do estabelecimento empresarial. Questão amplamente debatida e objeto de controvérsia é a destinação desses bens intangíveis por ocasião do afastamento de um sócio da sociedade empresária. Discute-se se esses bens devem integrar a base de cálculo dos haveres do sócio afastado. Neste trabalho, pretende-se oferecer resposta a essa indagação. Para tanto, analisaremos de que maneira são formadas as dimensões patrimoniais da sociedade - capital social, patrimônio líquido e estabelecimento -, as diversas hipóteses de extinção parcial do vínculo societário, o conteúdo econômico dos elementos intangíveis integrantes do estabelecimento e a natureza jurídica do eventual pagamento por esses bens ao sócio que se desliga da sociedade.
Keywords: Commercial law; Companies and partnerships; Direito comercial; Direito de recesso; Estabelecimento comercial; Goodwill; Sociedade comercial; Withdrawal rights

Le dirigeant de fait en droit privé français - Nze Ndong dit Mbele, Jean-Richard (Université Nancy 2, 2008)
Le dirigeant de fait exerce le pouvoir de gestion de la société en lieu et place des dirigeants régulièrement désignés ou avec ceux-ci. La société étant une personne morale dont l’organisation fait l’objet d’une attention particulière du législateur en raison de son importance dans l’économie moderne, l’intervention d’un dirigeant de fait suscite bien des interrogations quant à l’efficacité de ces règles. Cette thèse examine les circonstances historiques dans lesquelles la notion de dirigeant de fait est apparue dans le droit français applicable aux sociétés commerciales afin de cerner l’existence ou non d’une volonté du législateur d’autoriser ou d’interdire la direction de fait. Elle tente de contribuer modestement à la connaissance du statut de dirigeant de fait sur trois points principaux. Elle précise d’abord les conditions qui permettent d’attribuer à une personne la qualité de dirigeant de fait d’une société. Elle détermine ensuite les règles de droit qui sont applicables à un tel dirigeant. Elle propose enfin une théorie juridique pour justifier l’application de ces règles. Le résultat de la recherche permet d’affirmer qu’en dépit de la nature juridique originelle de son intervention, le dirigeant de fait jouit progressivement d’un statut de dirigeant social en droit français. The leader in fact exerts the power of management of the company instead of the regularly appointed leaders or with those. The company being a moral person whose organization is the subject of a special attention of the legislator because of his importance in the modern economy, the intervention of a leader in fact causes many interrogations as for the effectiveness of these rules. This thesis examines the historical circumstances in which the concept of leader in fact appeared in the French right applicable to the business firms in order to determine the existence or not will of the legislator to authorize or to prohibit the direction in fact. It tries to contribute modestly to the knowledge of the statute of leader in fact on three principal points. It specifies initially the conditions which make it possible to allot to a person the quality of leader in fact of a company. It determines then the legal provisions which are applicable to such a leader. She proposes finally a legal theory to justify the application of these rules. The result of research makes it possible to affirm that in spite of the original legal nature of his intervention, the leader in fact enjoys gradually a statute of social leader in French right.
Keywords: Dirigeant de fait; Droit commercial; Droit privé; France; Gestion d'entreprise

Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

La contribution de l'ordre juridique communautaire à la définition du siège social en droit international privé des sociétés - Mogavero, Clément (Université Jean Moulin Lyon 3, 2008)
La notion de siège social est fondamentale en ce sens qu’elle détermine la nationalité d’une société et fonde le rattachement juridique de cette dernière. Or, il n’existe pas de définition uniforme du siège social en droit international privé des sociétés. Au contraire, en matière de rattachement des personnes morales, le droit positif et prétorien se référent tantôt à la notion souple de siège statutaire, tantôt à celle de siège réel, plus contraignante. Les contours de la définition sont donc flous. Or, aborder le siège social semble désormais une nécessité pour répondre au besoin actuel de mobilité des sociétés. L’appréhension de la matière par le droit international privé s’avérant lacunaire, une clarification de ce concept établie par l’ordre juridique matériel et prétorien communautaire a semblée légitime. Or, celui-ci semble s’orienter vers une définition souple du siège statutaire, ce qui suscite un accroissement de mobilité des sociétés mais aussi un phénomène de law shopping, dont les effets néfastes sont dénoncés. Parallèlement, le rattachement au siège réel subsiste en droit communautaire, notamment à travers le règlement régissant la Société Européenne, cette dernière retenant la définition du siège réel. Ainsi, il apparaît un paradoxe puisque pour un même concept juridique, le droit communautaire retient deux définitions diamétralement opposées, lesquelles peuvent se compléter. En effet, la tendance, au sein de l’ordre juridique communautaire, confine à une domination du siège statutaire en qualité de rattachement principal des sociétés (Partie I). Néanmoins, dans un souci de protection des tiers et créanciers, le droit communautaire des affaires associe ces deux notions, en retenant, à titre subsidiaire, le rattachement au siège réel (Partie II).
Keywords: Droit européen; Droit international privé; Fusion d'entreprises; Sièges sociaux -- Transfert; Sociétés (constitution)

Le prix dans les cessions de droits sociaux - Stoclet, Mathieu (Université Lille 2, 2008)
Les promesses d'achat ou de vente de droits sociaux à prix garanti heurtent la prohibition des clauses léonines dès lors que leur prix est indépendant des résultats sociaux. Les clauses convenues par les parties et tendant à adapter le prix des droits sociaux à la valeur de la société dont les parts sociales ou actions sont cédées exposent par ailleurs le contrat à différents risques, notamment de nullité. Il conviendrait dès lors, afin de résoudre les difficultés pratiques résultant de l'application de ces règles, d'évincer sélectivement le droit de la vente et la prohibition des clauses léonines. On pourrait considérer, lorsque le cessionnaire des droits est animé par l'affectio societatis et lorsque le cédant connaît cette intention, que le contrat est un contrat innomé. Par ailleurs, une distinction au regard de la prohibition des clauses léonines entre les cédants qui en raison de leur affectio sicietatis peuvent être considérés comme partie au contrat de société, et les autres, pourrait être adoptée
Keywords: Cession d'actions; Cession de parts sociales; Contrat de société; Contrats; Corporate law; Droit des sociétés; Droits économiques et sociaux; France; Prix; Prix de vente; Prohibition des clauses léonines

Le gouvernement des groupes de sociétés. Les relations entre propriété et pouvoir à l'épreuve des réalités de l'entreprise contemporaine - Duet, Aurélie Catel (Université Grenoble 2, 2007)
Mon travail de thèse est orienté autour d'une approche sociologique des questions de gouvernance des groupes de sociétés. Ma recherche s'appuie sur huit études de cas de groupes français et internationaux, réalisées par le biais d'entretiens semi directifs auprès de dirigeants et cadres. En première approche, un groupe de sociétés est un ensemble d'entreprises organisé autour d'une maison mère et de filiales. Par définition, la maison mère détient plus de 50% du capital de ses filiales mais chacune des entités restent juridiquement indépendantes. Cette déconnexion entre la propriété des actifs et les frontières juridiques nous amène à nous questionner sur le statut de la propriété dans l'exercice du pouvoir. Dans cette perspective, ma thèse consiste à montrer que le groupe est une structure de gouvernement opportuniste. Cela signifie que la structure en groupe autorise les sociétés mères à déployer et à redéployer leurs prérogatives afin de tirer le meilleur parti des circonstances. La structure en groupe permet des changements de stratégie et c'est à l'aune de cette caractéristique que la vie des groupes devient compréhensible. On observe des manifestations de cet opportunisme dans ce que nous avons appelé des dilemmes de gestion. Ces dilemmes traduisent un opportunisme en acte. Ils concernent différents domaines de la vie des groupes : les relations économiques intragroupe, la discipline des dirigeants de filiale, la responsabilité des sociétés mères, la question des conflits entre société dominante et filiale. Ils « touchent » tous les groupes, quelque soit leur taille, leur secteur, leur âge. Ils traduisent des tensions et des alternatives que les groupes doivent trancher. Marché ou hiérarchie, subordination ou autonomie, pouvoir ou responsabilité, alignement des intérêts ou conflits sont différentes branches de ces alternatives. Cet opportunisme est rendu possible par une structure autorisant une pratique souple de l'exercice du pouvoir. En effet, la domination capitalistique de la maison mère lui permet de conjuguer deux rôles à priori nettement séparés : celui d'actionnaire et celui de manager. Cette domination capitalistique lui permet de déployer au maximum la palette de ses interventions : elle peut jouir de son rôle d'actionnaire et faire prévaloir un droit de gestion direct dans les affaires de ses filiales. Les sociétés mères mettent ainsi en œuvre l'ensemble des prérogatives des rôles attachés à l'actionnaire et au manager. Ils jouent, au gré des circonstances, sur des registres d'action variés et organisent ainsi un « pouvoir hybride ». On peut dès lors affirmer que c'est un besoin de flexibilité qui répond à l'émergence et au développement de la forme en groupe. Nous savons que l'environnement économique contemporain est marqué par de fortes incertitudes en matière économique, technologique, commerciale... Les managers sont à la recherche de structures qui permettent de « gérer » en souplesse ces incertitudes. Dans cette perspective, les groupes sont des architectures économiques qui permettent de trouver des capacités de gouvernement pour faire face aux incertitudes, en ayant la possibilité de paramétrer à volonté leurs systèmes de gestion.
Keywords: Groupes de sociétés; Pouvoir; Propriété

Directors’ duties to creditors - Lombard, Sulette (University of Pretoria, 2007)
Creditors of the corporate business form are in a vulnerable position. Recognition of the plight of corporate creditors led to the implementation of various legal measures aimed at protecting their financial interest in the company. These measures proved disappointingly inadequate in many instances. As a result the judiciary in some jurisdictions felt compelled to develop existing legal principles pertaining to directors’ duties in such a way that they could be used to facilitate protection of corporate creditors’ interests. This development did not meet with universal approval. Those opposed to the extension of directors’ duties to protect creditors’ interests have three main arguments against it. The first is related to conceptual issues and policy concerns. The second argument is that existing remedies are more than adequate to protect creditors’ interests. A last argument against a directorial duty to creditors pertains to the practical implementation of this extended duty. It is argued that the existing legal framework with regard to directors’ duties is not suitable to provide protection for creditors’ interests. However, it was shown in this study that the extension of directors’ duties to protect creditors’ interests is indeed justifiable on a sound conceptual basis and that policy concerns regarding such an extension are either unfounded, or should be addressed in some other way. An analysis of existing protective measures and remedies often referred to by opponents of an extension of directors’ duties, namely statutory personal liability of directors, traditional insolvency remedies, and the piercing of the veil doctrine furthermore showed that these measures are inadequate. This leads to the conclusion that there is a definite need for an alternative remedy, such as the extension of directors’ duties to include creditors’ interests. The existing legal framework in respect of directors’ duties furthermore proved to be capable of being successfully adapted to include creditors’ interests. Central issues in this respect, as was indicated by an analysis of case law, are the point in time when the duty to creditors is triggered, the beneficiary of the duty, in other words who would have locus standi in case of a breach of the duty, and the type of protection afforded to creditors’ interests by way of fiduciary duties and the duty of care and skill. The existing legal framework also provides measures in terms of which honest and diligent directors may be relieved from liability, such as indemnification, relief granted by the courts and director liability insurance. These measures, if formulated correctly, may achieve and maintain the essential balance between accountability and entrepreneurial freedom. The legislature appears to have adopted a cautious approach to the issue of directors’ duties to creditors. It thus seems to be up to the judiciary to develop directors’ duties to creditors in a meaningful way. Pioneering in this respect has already been done in Australia, New Zealand, England, Canada and the United States of America. It is to be hoped that the South African judiciary will follow suit when the opportunity to do so arises.
Keywords: Beneficiary of directors’ duties; Company law; Company’s interests; Corporate law

Legal aspects of corporate governance in the republic of South Africa: towards a possible model for improved stakeholder relations within the corporation - Spisto, Michael Paolo (University of the Witwatersrand, 2007)
Traditionally, company law assumes that the directors’ role is to run the company for the benefit of its shareholders alone and to maximise profits for them. It can be argued, however, that this view is too narrow and outdated; that is, company directors should have regard to the rights and interests of a broader range of corporate stakeholders. Hence, the question is whether we should change our perception of the company or corporation from one run by directors dedicated exclusively to serving the interests of shareholders to that of a corporation whose main purpose is to bring benefit not only to its owners and creditors, but also to its employees, the community and the environment. Given that reforms of directors’ duties in light of the above considerations have found their way into legislation across the globe, this thesis examines how and to what extent legal rules and policies should develop in South Africa to place directors under a positive duty to take account of the interests of bodies other than shareholders. Current South African company law does not contain clear rules regarding corporate governance issues and the duties and liabilities of directors. These matters have been left to the common law and Codes of Corporate Practice. Thus, there is no extensive statutory scheme in South Africa, which covers the duties, obligations and accountability of directors. The focus in this thesis is on the rights and interests of employees and the premise that is defended is that it is valuable to corporations to provide employees with an institutionalised voice at board level. It is argued that there is global evidence that where employees participate in the decision-making processes of the company, performance is generally enhanced. This, in turn, directly impacts upon and improves economic productivity, generating a ‘win-win’ situation. The question of the duties of company directors and managers is attracting much attention in South Africa. With rapidly developing and changing labour legislation in South Africa, it is essential to consider the extent to which the country should reassess its traditional principles of company law and corporate governance policies in order to encourage participatory roles for employees in the workplace. It is argued that if South Africa is to improve corporate productivity levels with its re-entry into international markets, management and labour must find improved ways of dealing with one another. The main purpose of this thesis, therefore, is to propose and formulate a workable corporate governance model for South Africa – one that would be advantageous to all stakeholders, especially the employees. This is achieved by comparing and contrasting international models of corporate governance and by applying the best features of each to the unique South African corporate system of values, structures and traditions. It is suggested that the current unitary board structure operating in South Africa has become outdated and does not provide employees with rights enabling them to engage in the decision-making processes of the corporation with their employees at an adequate level. In its place, a two-tier board system of corporate governance is proposed. The economic success of a company will bring about social benefits to many stakeholder constituencies. This will not happen if the company is a financial failure. The issue of obliging directors to act primarily for the benefit of shareholders alone is questioned. Corporate governance reforms were undertaken in many parts of the world in the late 1980’s and early 1990’s. This reform process questioned whether the interests of the company should be managed for the shareholders alone or for the other corporate stakeholders as well. There are many views that strongly support the idea that corporate governance should be seen as a system by which corporations are to be governed for the benefits of all stakeholders, including shareholders, employees, creditors, suppliers and the community. In this way, companies should be run as communities in partnerships with all their stakeholders. Thus, this thesis proposes that the success of a company is inextricably intertwined with a consideration of the rights and interests of its employees and other stakeholders.
Keywords: Bond/Debenture Holders; Community; Companies; Corporate governance; Corporations; Creditors; Employees; Environment; Interests; Models; Rights; Shareholders; South Africa; Stakeholder Relations

Les sociétés de gestion collective : contribution à l'étude du lien entre sociétés et auteurs ou artistes-interprètes adhérents - Balsan, Laurie (Université Jean Moulin Lyon 3, 2007)
Les mérites de la gestion collective sont immenses. Les auteurs et artistes-interprètes sont le plus souvent des individus isolés. Pour eux, le libre jeu du marché aurait de fortes chances de se traduire par des conditions de rémunération misérables. L'ensemble de la doctrine s'accorde d'ailleurs à dire que le choix d'une gestion individuelle des droits serait source de difficultés pratiques considérables pour l'auteur ou l'artiste « isolé ». L'impuissance des titulaires de droits à effectuer eux-mêmes cette gestion commande donc, en pratique, de recourir à une société de gestion collective. Il est possible de soumettre une définition des sociétés de gestion collective formulée comme suit : « sociétés civiles particulières dont les associés présentent la qualité de titulaires de droits de propriété littéraire et artistique ; droits, par eux mis en commun, dans le but de les voir administrer. La mission de gestion collective à la charge de ces sociétés consiste principalement dans le contrôle et la défense desdits droits, la promotion des intérêts de leurs membres, et surtout, la délivrance, pour le compte de leurs adhérents, d'autorisations d'exploitation, puis la perception des rémunérations qui s'y rattachent et leur répartition ». De façon évidente, ces sociétés se trouvent au carrefour de multiples droits. Pour résumer, sur une base de droit commun interagissent non seulement le droit de la propriété littéraire et artistique et le droit des sociétés, mais aussi le droit des biens, le droit de la concurrence, le droit communautaire, et d'autres droits spéciaux à des degrés différents. En outre, si l'on se réfère à certains arrêts, il semble qu'il existe un régime spécifique, propre aux SGC, une sorte de droit « ultra spécial » : le « droit des SGC ». Pour le cas des SGC, le cloisonnement du droit en différents droits spéciaux mène à un régime flou et parfois parfaitement incohérent dont elles paraissent tirer profit en pratique. La finalité de cette thèse est d'éclaircir l'ensemble des règles applicables aux SGC et plus précisément au lien tissé entre la société et ses adhérents. L'objectif de ces travaux est de faire ressortir, s'agissant de ce rapport, un régime juridique cohérent. Quels sont les droits qui ont vocation à s'appliquer aux SGC et comment arriver à une complémentarité cohérente entre eux ? Il s'agit donc d'un travail de rationalisation qui impose de remettre en cause le droit applicable aux SGC et de le repenser « de lege ferenda ».
Keywords: Competencia; Concurrence; Contrats de gestion; Corporate law; Droit d'auteur; Droit des biens; Droit des sociétés; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Contrôle de droit, contrôle de fait - Nawatrakulpisut, Somsak (Université Jean Moulin Lyon 3, 2007)
Notion élaborée, en France, dès le milieu des années 1980 par la doctrine et la législation, le contrôle connaît aujourd’hui un important essor dans la plupart des disciplines juridiques françaises, et notamment en droit des sociétés. Malgré le défaut de véritable définition légale, car le législateur se cantonne à une énumération d’indices faisant apparaître son existence, sa présence, le terme « contrôle » a gagné une nouvelle conception contemporaine, celle de la situation de domination d’une société sur une autre. Dans une telle perspective, le législateur du droit des sociétés a donc pris en compte les différentes hypothèses susceptibles d’aboutir à une telle situation. Parmi ces diverses modalités de contrôle, nous pouvons constater que le contrôle se réfère, en principe, aux droits de vote absolus; mais il peut aussi résulter d’autres éléments de fait. De ce constat, découle un double volet du contrôle-domination : le « contrôle de droit » fondé sur la détention nécessaire de la majorité des droits de vote dans une société cible; et le « contrôle de fait » tenant à un faisceau d’indices et non à ces prérogatives absolues. Ces deux approches pratiques du contrôle supposent non seulement de dégager les traits particuliers qu’elles présentent, mais aussi d’envisager les implications juridiques et financières auxquelles ces contrôles peuvent donner lieu. Ceux-ci constituent, enfin, les critères de base pour élaborer des règles de surveillance, tant sur les détenteurs, que sur les stratégies de ce pouvoir de domination.
Keywords: Actionnaires minoritaires; Assemblées d'actionnaires; Conventions entre actionnaires; Corporate law; Droit des sociétés; France; Offres publiques; Pactes d'actionnaires; Sociétés; États financiers consolidés

Levantamiento del velo societario y los derechos, deberes y responsabilidades de la sociedad anónima - Guerra Cerrón, Jesús María Elena (Universidad Nacional Mayor de San Marcos, 2007)
En el año 2004 este tema, si bien aún no era muy conocido en el Perú, había sido desarrollado por algunos abogados y profesores peruanos, e incluso a la fecha encontramos artículos importantes en revistas jurídicas acerca del levantamiento del velo societario y libros sobre el uso fraudulento de la persona jurídica. Por lo tanto, no puedo decir que el presente trabajo sea original en su totalidad, pero sí me permito afirmar que lo es en cuanto a la forma de abordarlo, su desarrollo y posición final asumida. El trabajo se ha desarrollado en once capítulos, debiendo desde ya precisarse que si bien hay una alusión general a las personas jurídicas, el tema central es la sociedad anónima ordinaria o clásica como se le denomina (ya que no han sido consideradas en el estudio las particularidades de sus dos modalidades: sociedad anónima cerrada y sociedad anónima abierta), la que además es reconocida como una conquista económica, jurídica y social, habiendo una notoria y gran diferencia con las “otras formas societarias” que también están reguladas en la Ley General de Sociedades, pero que sin embargo no cumplen un papel importante en la economía del país.
Keywords: Derecho comercial; Personas jurídicas; Responsabilidad (Derecho); Responsabilité; Sociedades anónimas; Société Anonyme

La escisión de sociedades y el efecto económico de concentración empresarial - Ramos Almeida, Carlos Oscar (Universidad Nacional Mayor de San Marcos, 2007)
La escisión es una herramienta de mucha utilidad e importancia para la reorganización de empresas, con el fin de alcanzar objetivos económicos y societarios de gran trascendencia para las personas jurídicas y naturales involucradas; permitiéndole al empresario, disponer de mecanismos para la reinserción en el mercado local y exterior de condiciones competitivas de precio, calidad, cantidad y oportunidad; logrando así una mejor utilización de su patrimonio en la creación de riqueza. Cabe señalar que al legislador le interesa que las empresas produzcan más y mejor, razón por la cual en todos los países el ordenamiento jurídico no sólo evita poner trabas a la reorganización empresarial, sino que provee de los medios necesarios para estimularla y facilitar su ejecución. Al Derecho le cabe desempeñar un rol fundamental, el de ordenar, guiar a las demás disciplinas aplicables y organizar las relaciones jurídicas que emanan de los diferentes procedimientos de reorganización, otorgando la debida seguridad jurídica para preservar los derechos de todas las personas intervinientes. Vemos pues como el Derecho no es ajeno a esta exigencia de adaptación de la estructura de la empresa. El ordenamiento jurídico y la doctrina han ido definiendo el marco normativo que sirva de sustento a los procesos generados en la práctica empresarial procurando fundamentalmente una simplificación de su formulación jurídica. A esta finalidad responde nuestro Derecho Comercial a través de mecanismos como la transformación, fusión, escisión, reorganización simple y figuras combinadas y múltiples, que inciden tanto en su estructura económica como en la jurídica.
Keywords: Derecho y legislación; Empresas; Fusión; Ley de sociedades anónimas

La transmisión de acciones y participaciones sociales con prestaciones accesorias - López García, Oscar (Universidad de Sevilla, 2006)
Todo trabajo de investigación presupone siempre una causalidad y unos objetivos en perfecta armonía con la máxima escolástica:finis est primus inintentionem, ultimus in executionem. En consecuencia, el objeto de nuestra investigación, en relación con esa máxima, es el estudio de la transmisión de acciones y participaciones sociales con prestaciones accesorias, a sabiendas de que dicha transmisión en las sociedades de capital ha planteado siempre, en nuestro Derecho, una gran complejidad técnico-jurídica -sobre todo cuando nos encontramos con prestaciones accesorias de carácter personalísimo, y no sólo por la falta de previsión legal, sino también por la inexistencia de un tratamiento doctrinal adecuado y una escasa atención jurisprudencial-, y de que es igualmente constatable que tampoco el Derecho comparado aporta soluciones a nuestro supuesto, quizás porque predomina fuera de nuestras fronteras el sistema de cuota única o por cabeza. Para poder desarrollar convenientemente este estudio es metodológicamente positivo dividir el trabajo en tres capítulos. El primero de ellos analiza la prestación accesoria como parte integrante de la posición jurídica de socio y las especialidades que plantea la transmisión de la cuota social a la que aparece vinculada la prestación. Entendemos que es inexcusable profundizar en este tema, antes de afrontar el análisis del régimen jurídico-positivo de transmisión de acciones y participaciones sociales con prestaciones accesorias previsto por nuestro legislador.

Le sort des contrats dans les opérations de fusion et de scission de sociétés commerciales - Albortchire, Adamou (Université d'Auvergne - Clermont-Ferrand 1, 2005)
Les Contrats sont des outils omniprésents dans la vie de l'entreprise commerciale et conditionnent, dans une large mesure, son activité économique. Or, plusieurs évènements peuvent, au cours de son existence, affecter son évolution parmi lesquels on peut noter les fusions et scissions. Dès cet instant, deux questions peuvent se poser en ce qui concerne le sort aprticulier des contrats à son actif. Ceux-ci sont-ils supposés se poursuivre en dépit de la disparition de la personne morale contractante ? Ou, au contraire, sont-ils voués à disparaitre au même titre qu'elle ? En d'autres termes, ces opérations sont-elles constitutives de causes de caducité principielle du contrat ? Dans le cas ou ces contrats seraient destinés à poursuivre, le sont-ils tous ? La loi du 5 janvier 1988 qui a réformé et modernisé le régime juridique des fusions et scissions ainsi que la jurisprudence nous ont donné des réponses. Il est, de façon générale, admis que les opérations susvisées se caractérisent par le fait qu'elles impliquent la transmission universelle du patrimoine de la société qui disparaît au profit de la ou des sociétés bénéficiaires. Le principe de poursuite de l'activité contractuelle étant général et automatique, puisque la transmission est "universelle", il s'applique, par cons"quent, à tous les contrats en cours, quels qu'ils soient, de l'entreprise contractante dissoute sans liquidation. Cependant, ce principe, fût-il général, ne se révèle pas pour autant absolu. C'est à dire qu'il comporte malgrès tout des limites. C'est le cas, par exemple, lorsque soit une disposition légale spécifiques, soit une clause de non transmission adéquate empêchent la poursuite automatique du contrat.
Keywords: Contrats; Droit des sociétés commerciales; France; Fusion d'entreprises

La participation des collectivités territoriales au capital de sociétés - Peltier, Marc (Université Paris 1, 2005)
La législation française se fonde traditionnellement sur un conflit entre l'intérêt général, le but lucratif et le risque d'entreprise. La participation des collectivités territoriales au capital de sociétés est alors en principe interdite. De nombreux textes autorisent cependant des collectivités territoriales à participer au capital de sociétés spécifiques. La protection de l'intérêt général et l'accueil des collectivités territoriales se font dans des groupements qui dérogent au droit commun des sociétés. Ces régimes sont porteurs de risques tant pour la société elle-même que pour les collectivités territoriales. Une autre approche de la participation des collectivités territoriales au capital de sociétés devrait être envisagée. Le droit communautaire pourrait servir de référence en s'inspirant du critère de l'investisseur privé en économie de marché. La transposition en droit interne de ce critère permettrait de faire évoluer le régime de ces sociétés vers le droit commun.
Keywords: Administration locale; Capital social; Droit commercial; France; Investissements de capitaux; Sociétés d'économie mixte

La Caducidad de instituciones y actos, derechos y obligaciones en la ley general de sociedades plazos y procesos propuestas de reforma - Beaumont Callirgos, Ricardo Arturo (Universidad Nacional Mayor de San Marcos, 2004)
Bajo el título LA CADUCIDAD DE LAS INSTITUCIONES Y ACTOS, DERECHOS Y OBLIGACIONES EN LA LEY GENERAL DE SOCIEDADES, PLAZOS Y PROCESOS, PROPUESTAS DE REFORMA, el autor de este trabajo de investigación pretende el alto honor de alcanzar el grado académico de Doctor en Derecho, nada más y nada menos que en la Universidad Nacional Mayor de San Marcos, Universidad del Perú, Decana de América. No me detendré a explicar acá, la naturaleza jurídica y las características de la caducidad, ni sus diferencias y semejanzas con la prescripción. Para ello existen numerosas páginas, bastante contenido, significativos ejemplos, abundante opinión de la doctrina y legislación nacional y extranjera, en la tesis que se alcanza. Más bien, es pertinente la explicación acerca de, a qué instituciones y a qué actos se refiere, y si podemos tener ejemplos de derechos y obligaciones, en la Ley General de Sociedades. CABANELLAS afirma que Institución es Establecimiento, fundación, creación...Lo fundado o establecido.... Nombramiento o designación de heredero o legatario. Cada una de las materias principales del Derecho o de alguna de sus ramas; como la personalidad jurídica y la familia dentro del Derecho Civil; o, en sucesivo análisis, la patria potestad en la familia; o el derecho de corrección, en el conjunto de atribuciones de la autoridad paterna. Un ejemplo de institución en materia societaria podría ser justamente la personalidad jurídica de las sociedades. El art. 6° de la Ley 26887 establece que “La sociedad adquiere personalidad jurídica desde su inscripción en el Registro y la mantiene hasta que se inscribe su extinción”. La ley es clara. Sin embargo, podríamos hablar de caducidad de la personalidad jurídica cuando la sociedad continúa en actividad no obstante haber incurrido en causal de disolución prevista en la ley, el pacto social o el estatuto, según la disposición contenida en el art. 423° inciso 6., y teniendo a la vista los arts. 424° y 430° de la acotada norma?. Con la personalidad jurídica el sujeto de derecho posee un blindaje que lo protege y le permite actuar como otra persona, pudiendo celebrar en tanto tal, contratos, asumiendo derechos y deberes, y es en este orden de ideas que por ejemplo el art. 78° del Código Civil expresa que “La persona jurídica tiene existencia distinta de sus miembros y ninguno de éstos ni todos ellos tienen derecho al patrimonio de ella ni están obligados a satisfacer sus deudas”. Cuando se cae en irregularidad, se quiebra, se rompe el blindaje, y tan es cierto que el precitado art. 430° de la Ley General de Sociedades expresa que “... los acreedores particulares de los socios concurrirán con los acreedores de la sociedad irregular para el cobro de sus créditos, teniendo en cuenta la prelación que conforme a ley corresponda a dichos créditos”. Instituciones del derecho societario como la personalidad jurídica de las sociedades, la constitución de sociedad por oferta a terceros, la junta general de accionistas, el directorio, el derecho de separación, la reorganización societaria o la liquidación de sociedades, serán revisadas acá, desde la óptica de su caducidad. A eso nos referimos en el título del trabajo. En materia societaria, son “actos” sociales, la misma escritura pública de constitución así como sus modificaciones, y también los acuerdos que adoptan sus órganos, llámense éstos, directorio o junta general. El art. 5° de la Ley establece que “La sociedad se constituye por escritura pública, en la que está contenido el pacto social que incluye el estatuto. Para cualquier modificación de éstos se requiere la misma formalidad. En la escritura pública de constitución se nombra a los primeros administradores, de acuerdo con las características de cada forma societaria. Los actos referidos en el párrafo anterior se inscriben obligatoriamente en el Registro del domicilio de la sociedad. Cuando el pacto social...” (la cursiva es nuestra). Conste que la expresión “actos”, y por ende su concepto y presencia en la vida institucional de las sociedades, es significativa, tan es cierto que en las Reglas Generales Aplicables a Todas las Sociedades, aparece en más de una decena de veces, en sus arts. 7°, 11°, 12°, 13°, 14°, 16°, 17°, 18°, 21°, 46 y 49° relativos a actos anteriores, objeto social, actos ultra vires, actos que no obligan a la sociedad, poderes, plazos para solicitar inscripciones, ejercicio de poderes no inscritos, sucursales, copias certificadas y caducidad, respectivamente. Respecto a derechos y obligaciones, caducibles o no, podemos referir, por ejemplo, la nulidad de acuerdos societarios, la responsabilidad de los fundadores, la cobranza de los dividendos pasivos y su responsabilidad por el pago, la prenda de acciones, la convocatoria a junta general solicitada por accionistas, las vacancias múltiples en el directorio, la responsabilidad civil de los directores y gerentes, el derecho de separación, la oposición a la reducción de capital, el cobro de dividendos, el derecho de adquisición preferente en las sociedades anónimas cerradas, la responsabilidad de los Liquidadores, entre otros. El estudio de la caducidad tiene que estar estrechamente vinculado al decurso del tiempo porque con él y a partir de él, las personas naturales y jurídicas, y también las sociedades de facto o irregulares, adquieren o pierden derechos, adquieren o concluyen obligaciones. No podemos prescindir de los “plazos”. Y parte del estudio e investigación que se realiza acá está vinculada a establecer si la Ley General de Sociedades ha sido cuidadosa en prever con suma claridad no solamente si existen los plazos perfectamente definidos sino y en particular si se ha cuidado en establecer el día que sirve de punto de partida, el día inicial para el cómputo. Esto es sumamente importante; no olvidemos que el art. 2007° del Código Civil establece que “La caducidad se produce transcurrido el último día del plazo, aunque éste sea inhábil”. El cómputo de un día, de unas horas, puede significar adquirir derechos o perderlos irremediablemente. Y no podremos dejar de hacer cita a los “procesos” y una breve referencia a su cauce, su trámite, sus etapas principales, aunque para no ser repetitivos, lo formularemos una sola vez y a partir de entonces, se hará expresa cita del lugar en que lo hemos desarrollado, para su adecuado y rápido hallazgo. Éste es el esfuerzo que con entusiasmo y empeño, emprendemos. Esperamos llegar a conclusiones valiosas aunque lo fundamental, para nosotros, es que este trabajo pueda servir para el desarrollo de otros, que abra ruta, que abra camino a otros esfuerzos similares, para beneficio del desarrollo, en nuestro país, del Derecho Mercantil en general y el Derecho Societario en particular. Abordar, investigar y estudiar cualquier tema societario es verdaderamente fascinante, motivador. Entusiasma. Se deja de hacer cualquier otro encargo, profesional o no, y se separa el tiempo necesario para hacerlo. De verdad. Y es que en nuestro Perú, desde siempre, la Ley de Sociedades (N° 16123, Mercantiles, de 1966; y arts. 1686° a 1748° en el Código Civil de 1936) ha sido la Ley de las Empresas. Claro que antes de la citada 16123, deberíamos referirnos al Código de Comercio de 1902, aun hoy formalmente vigente, en cuyos artículos 124° a 181° se regulaban las denominadas Compañías Mercantiles, y cuyo art. 966°, el último del Código, hacía expresa cita, como única Disposición Transitoria, a lo siguiente: “Las compañías anónimas existentes con anterioridad a la publicación de este Código, conformarán sus respectivos estatutos a las disposiciones en él contenidas, dentro del plazo de noventa días”. Y en tanto regulación jurídica de las empresas, resulta particularmente acogedor. Empresa, emprendere, acometer algo, iniciar algo con determinados fines o propósitos; y en lo económico, “organización dedicada a la producción, transformación, circulación o comercialización de bienes, o a la prestación de servicios, socialmente responsable, es decir, que su objetivo y acción no se circunscriben sólo a los términos económicos, sino a su involucramiento con la sociedad, su comunidad y con su propio entorno. Puede ser organizada por persona natural o jurídica”. Entonces, la mixtura de estudio, juridicidad y empresa, la empresa como organización jurídica, la normativa jurídica al interior y exterior de la empresa, etc., etc., es lo que le da el sabor al estudioso del Derecho, al fanático, al investigador de las ciencias jurídicas, y en particular a los de las ciencias jurídicas societarias, empresariales, para escribir obras sobre la materia y difundir, a través de la docencia, esta interesantísima disciplina, y también para procurar, para intentar llegar a los niveles que llegaron nuestros maestros, en particular nuestros maestros sanmarquinos, los de nuestra alma mater, Universidad del Perú, Decana de América. Y no vamos a remontarnos en esta investigación a los Códigos de Comercio de España y de Perú de 1829 y 1853, respectivamente, pues carecería absolutamente de sentido. Aquí, vamos a partir propiamente, de la Ley 16123 y sus referentes, los anteriores, el Código de Comercio de 1902 y leyes conexas, Código Civil de 1936, de Bancos y otras; y los posteriores, D. Leg. 311, Ley General de Sociedades de 1985, y leyes conexas, Código Civil de 1984, de Bancos, D. Leg. 637 del 25 de abril de 1991, D. Leg. 770 del 30 de Octubre de 1993 y Ley 26702 del 09 de Diciembre de 1996 y otras. Ahora bien, cómo no va a ser fascinante, por ejemplo, abordar el tema doctrinario de la naturaleza jurídica de la sociedad y sus diferentes teorías, la contractualista, la institucionalista, la del acto jurídico complejo, la del contrato atípico, la del contrato de prestaciones pluripersonales autónomas, etc., etc. Estudiar si toda sociedad persigue fin lucrativo o no, y las diferencias, en todo caso, del concepto lucro, con los denominados beneficios, con las utilidades, con las ganancias, con los márgenes de rentabilidad y por supuesto, con los excedentes de presupuesto. Las formas de constituir una sociedad, su personalidad jurídica y los convenios entre socios. La denominación y la razón social de las sociedades de capitales y de personas, respectivamente. El objeto social y los actos ultra vires. El domicilio de la sociedad y las sucursales. Los aportes de bienes muebles e inmuebles, dinerarios y no dinerarios, corporales e incorporales, tangibles e intangibles, registrables y no registrables, registrados y no registrados, etc. La valuación de los aportes, su saneamiento y el riesgo y pérdida antes de su entrega. Los beneficios y pérdidas, el reparto de utilidades, las copias certificadas, y el arbitraje y conciliación como mecanismos alternativos para la solución de los conflictos. Y todo este maravilloso arsenal temático es sólo un extracto de títulos contenidos en el Libro Primero, faltando por desarrollar el Libro Segundo, sobre la Sociedad Anónima; el Libro Tercero, que respecta a las Otras Formas Societarias –sociedad colectiva, sociedad encomandita simple, sociedad encomandita por acciones, sociedad comercial de responsabilidad limitada, sociedad civil ordinaria y sociedad civil de responsabilidad limitada; y el Libro Cuarto relativo a Normas Complementarias, el cual, a pesar de un título o etiqueta que dice casi nada –normas que le adicionan, que le agregan-, contiene materias tan interesantes como el de la Emisión de Obligaciones –que tal vez encontraría mejor ubicación en la Ley del Mercado de Valores, porque los Bonos u Obligaciones, en tanto Títulos Valores ya se hallan definidos, por supuesto, en la Ley de Títulos Valores 27287- Transformación, Fusión, Escisión, Disolución, Liquidación y Extinción. Hago caso omiso al Libro Quinto, sobre Contratos Asociativos –Asociación en Participación y Consorcio- porque éstos son contratos de empresa o contratos de colaboración empresarial, y si bien están nítidamente emparentados con las sociedades no tienen porque habitar en su misma casa. Este Libro Quinto pasará en breve, esperamos, a la Ley Marco del Empresariado y la Ley General de Sociedades dejará de tener cuatrocientos cuarenta y ocho artículos para quedar solamente con los que debe tener, es decir, cuatrocientos treinta y siete.
Keywords: Droit des sociétés; Empresas (Derecho y legislación); Ley de sociedades anónimas; Obligaciones (Derecho); Perú; Prescripción (Derecho)

Corporate governance: a practical and effective response to the challenges raised - Fridman, Josef J. (McGill University, 2004)
This thesis seeks to address corporate governance from both a practical as well as an academic perspective. It searches for solutions to self-interest and agency costs, problems that it is posited are innate to the anthropomorphism of the corporation and to the separation of management and ownership of widely held, publicly traded, corporations. Practically, this dissertation is anchored in experience, garnered from empirical research, based on in depth and general surveys, as well as detailed interviews. It examines the workings of corporations, including their boards of directors, of gatekeepers, of checks and balances and of shareholders and the relative importance and rationale for the roles that they play. Based on the academic and empirical efforts it is posited that self-interest and the funneling syndrome, (a process whereby information required for decision making is constrained and managed by those in control), almost always predetermines the outcome of the corporate formal decision making process involving the board of directors. This facilitates abuse. When it occurs and there appears to be no accountability, confidence essential to the capital markets, quite understandably, suffers. A hypothesis is advanced to explain the complexity of a potential failure of corporate governance through a relatively simple formula. It draws conclusions as to what is required to help address the challenges raised by the breakdown in effective corporate governance and to help instill greater investor confidence. A self-assessment mechanism to help quantify how effectively a corporation is dealing with corporate governance, both on an absolute basis (comparing itself year over year) and on a relative basis (compared to one's peers) is proffered. This tool of more effective corporate governance, seeks to identify the causes for breakdowns in corporate governance and to assist a board of directors in dealing more proactively with this challenge.
Keywords: Corporate governance

Reflexiones sobre la transparencia en la información en el mercado primario de bonos corporativos - García Mori, Luis Miguel (Universidad Nacional Mayor de San Marcos, 2004)
El presente trabajo tiene como objetivo plantear algunas reflexiones sobre la transparencia en el mercado primario de bonos corporativos, dentro de un contexto posterior a la crisis asiática de 1997, la crisis rusa de 1998, la crisis del Brasil de 1999, y los escándalos corporativos de los años 2001 y 2002 de Enron, Worldcom y Tyco, que incrementaron la preocupación por las prácticas de Buen Gobierno Corporativo, que se fundamentan en la transparencia de la información que es proporcionada a los mercados financieros. La referencia que se ha tomado en el mercado financiero corresponde a las 18 emisiones de bonos corporativos colocados durante el año 2001, complementando el análisis con una muestra de seis emisiones, tres en dólares y tres en soles, para cada unos de los años siguientes 2002, 2003 y 2004. Los mercados financieros pueden ser clasificados en función al plazo: en mercado de dinero y de capitales, en función a la entrega: en mercado al contado o a plazo, en función a la emisión: en primario y secundario, en función a la obligación: en mercado de deuda y de acciones, en función al ámbito geográfico: en mercado local e internacional, en función al mecanismo centralizado de negociación: en mercado bursátil y extrabursátil, en función de la oferta: la misma puede ser pública o privada. Los mercados financieros permiten la transferencia de fondos, la redistribución del riesgo, determinan el precio y el rendimiento, proporcionan liquidez y reducen costos de búsqueda e información. Un mercado es el encuentro de ofertantes y demandantes, y en el caso de los mercados financieros, estamos ante el encuentro de ofertantes y demandantes de instrumentos financieros. Un instrumento financiero o activo financiero representa un derecho sobre un activo real o sobre el patrimonio o sobre los flujos futuros que genere, en tal sentido, su valor se obtiene al traer al presente, mediante una tasa de descuento, los flujos futuros que genere. La tasa de descuento es la tasa de interés que corresponde el rendimiento exigido por el inversionista en función al riesgo del valor, y representa el costo del dinero. En tal sentido, a mayor información respecto al instrumento financiero menor riesgo, y por ende, mayor valor del mismo, por consiguiente la transparencia que significa mayor información crea valor para el instrumento financiero y para el inversionista. La constitucionalización del Derecho del mercado ha sido un largo proceso histórico, ha representado la evolución del Derecho mercantil, desde el Derecho del comerciante, y los actos de comercio, hasta el derecho del mercado. En la actualidad, si bien se ha incluido la referencia al mercado de bienes en la Constitución, aún está ausente el mercado de capitales del texto constitucional. Recién con la Constitución de 1979 se incorporó al Banco Central en el texto constitucional, y se le encargó la estabilidad monetaria, la cual es la base para la emisión de instrumentos financieros, dado que la tasa de interés nominal incluye el riesgo de inflación. Sin embargo, no obstante este “deber constitucional”, su grado de incumplimiento alcanzó la cúspide en 1990 cuando la inflación superó el rango del siete mil por ciento anual. Las reflexiones que se presentan en el presente trabajo tratan de evidenciar los “conflictos de interés” y la “falta de transparencia” en el mercado primario de bonos corporativos y en la administración de las sociedades, en un tiempo en que el mercado de capitales en nuestro país es aún incipiente, pero que muestra una tendencia al crecimiento, lo que en el breve plazo exigirá un replanteamiento o perfeccionamiento de su regulación.
Keywords: Bolsas de valores; Bonos; Inversiones

La société, technique d'organisation du patrimoine - Labelle-Pichevin, Fabienne (Université de Rennes 1, 2003)
La société est une technique au service d’objectifs patrimoniaux désormais primordiaux. Elle répond à ces préoccupations patrimoniales, car elle est une véritable organisation : elle agence pour procurer un meilleur état au patrimoine. En premier lieu, la société structure le patrimoine à deux niveaux. En externe, le patrimoine est regardé dans sa globalité. La technique sociétaire réalise une séparation des éléments patrimoniaux à affecter. Elle permet alors de les isoler, le plus souvent dans une optique de protection. En interne, le patrimoine est regardé dans sa composition. La société modifie son mode d’administration. Après la réalisation d’apports, le titulaire du patrimoine dispose d’un nouveau mode de détention qui diffère de la propriété initiale. Le pouvoir ainsi obtenu favorise la transmission du patrimoine. En second lieu, ces nouveaux aménagements valorisent le patrimoine de deux manières. Directement, la société favorise sa croissance. Les nouvelles formes le représentant stimulent son développement. La société permet ainsi de se constituer un patrimoine ex nihilo en opérant une patrimonialisation de la force de travail. Elle est également un mode de fructification du patrimoine. Indirectement, le patrimoine est valorisé, quand la société optimise sa situation par rapport aux contributions fiscales. Elle ménage une paix fiscale aux revenus du patrimoine et des économies fiscales aux valeurs du patrimoine. Ces effets secondaires valorisants de la structuration sont autant recherchés que l’aménagement effectué par la société. Cet emploi a toutefois un effet pervers : l’activité économique de la société peut être entravée lorsque la finalité principale devient patrimoniale. La technique perd alors tout intérêt : le tassement de l’activité freine l’enrichissement. Une hiérarchie des priorités s’impose. En réalité, la société doit rester plus qu’une technique et affirmer sa personnalité juridique au service de son activité et de son propre patrimoine.
Keywords: Actions; Fiscalité; Force de travail; Parts sociales; Patrimoine; Personnalité morale; Société; Transmission

Le désengagement de l'Etat de la gestion des affaires économiques : une solution à la crise des entreprises publiques du Sénégal - Badji, Marie Suzanne (Université Cheikh Anta Diop, 2002)
Keywords: Entreprise publique; Etat (désengagement); Gestion; Sénégal

Community competence to control mergers : the jurisdictional divide - Burnley, Richard (European University Institute, 2002)
Keywords: Antitrust law; European Union countries; Unfair Competition

Globalization and the limits of National merger control laws: gaps in global governance and the need for an international merger control regime - Wilson, Joseph (McGill University, 2002)
From an economic perspective, globalization is dismantling national barriers to entry and is transforming domestic markets into a global market. To meet the challenges posed by the integration of markets, corporations are joining forces with their former competitors to expand their presence in the global market. Rapid growth in transnational mergers to create global corporations is one of the key features of globalization. As multinational corporations are uniting, so should antitrust agencies that regulate them. Antitrust agencies around the world are realizing that the consumers whom they are mandated to protect are being adversely affected by decisions made beyond their national borders. By using the "effects" test, countries bring within their jurisdiction review of any merger or acquisition involving foreign companies with significant revenue or assets within their jurisdiction. The proliferation of merger control laws, in the absence of a mechanism to coordinate the transnational merger review, places an unnecessary burden on merging parties, and runs the risk of divergent outcomes, which at times cause friction among nation-states. Both to alleviate unnecessary burdens imposed on corporations and to reduce inefficiencies produced by the disparate review of a single transnational merger by several countries, this thesis proposes an International Merger Control Regime integrated into the WTO. The proposal focuses on ways to operationalize a "Lead Jurisdiction" model of oversight rather than on the creation of a new supranational decision-making agency. WTO dispute settlement and arbitration would be used to resolve conflicts arising out of the inability of a Lead Jurisdiction to arrive at an outcome satisfactory to other significantly affected jurisdictions.
Keywords: International merger control; Merger; Merger control

Les nullités en droit des sociétés - Robert-Cadet, Isabelle (Université Jean Moulin Lyon 3, 2000)
La sanction de nullité n’est pas « un remède mais un toxique » écrivait Joseph HEMARD dans son traité sur les sociétés de fait au siècle dernier. Qu’en est-il au XXIème siècle ? De toute évidence, celle-ci n’a pas sombré dans les oubliettes du droit des sociétés. En droit civil, l’annulation sanctionne le non-respect des conditions de validité dans la conclusion des actes juridiques. Passée au prisme déformant du droit des sociétés, elle se présente toujours comme la sanction traditionnelle de la violation de l’ordre public sociétaire, exprès ou tacite, dans la formation des actes en la matière. Mais, son champ d’application se limite parfois à une peau de chagrin et les dérogations dans son régime sont légions. Car, par nature, les constitutions de personnes morales, les délibérations d’assemblées générales ou de conseils d’administration, les décisions et nominations des instances dirigeantes voire les pactes d’actionnaires appartiennent à la catégorie des actes juridiques collectifs, c’est-à-dire des manifestations de volonté, concordantes et interdépendantes dont l’intérêt est commun. Les sociétés et leurs modalités de fonctionnement ne relèvent pas de la définition des contrats puisque les obligations des associés, les uns envers les autres, ne sont ni réciproques, ni antagonistes : les statuts fixent un cadre permettant de réaliser l’objet social dans le but de partager les bénéfices qui en résultent. A l’aune de l’acte collectif, les nullités en droit des sociétés connaissent, en revanche, un fondement spécifique unique à partir duquel un régime autonome, homogène et cohérent s’est élaboré de façon empirique. Il apparaît en effet que les distinctions bipartites entre, d’une part, nullités textuelles et nullités virtuelles et, d’autre part, nullités absolues et relatives, ont fait long feu. Les nullités sont surtout relatives car les intérêts à protéger, en droit des sociétés, sont éminemment collectifs. Les nullités sont également virtuelles pour l’essentiel : c’est la norme en cours de vie sociale et, la pratique en dénombre plus d’un cas pour frapper les vices de constitution, puisqu’en l’absence de véritable contrôle dans la formation des sociétés, le carcan trop étroit des nullités textuelles a explosé. Malgré les effets perturbateurs de l’annulation des sociétés, le droit interne français n’a pas pu, il est vrai, dans ce contexte, supprimer totalement les nullités de fond ; seules les nullités de forme ont fait l’objet d’une véritable purge lors des réformes sur les sociétés. Quoique d’application délicate, les nullités de procédure subsistent comme sanction des vices de fonctionnement dans les sociétés. Compte tenu des divergences avec le droit communautaire concernant les restrictions des cas de nullité de sociétés par actions, le risque d’une action en manquement contre l’Etat français est patent! Dans l’attente d’une nouvelle directive relative au fonctionnement des sociétés, le sujet conserve, nonobstant un contentieux assez faible, toute son actualité et un intérêt juridique certain. Néanmoins, une véritable stratégie d’évitement des nullités s’est mise en place depuis plusieurs siècles pour les besoins de la sécurité juridique. Devenue facultative en droit positif, à défaut d’être complètement éradiquée, cette sanction revêt parfois même un caractère subsidiaire ! Aussi la théorie des sociétés de fait a-t-elle été absorbée, sans autre forme de procès, par le principe de non-rétroactivité. Les actes collectifs de société sont devenus annulables : ils demeurent valables jusqu’au prononcé de l’annulation. Non remis en cause rétroactivement, les actes qui en découlent continuent par conséquent de produire leurs effets au-delà de l’annulation. Le concept de nullité pour l’avenir est né. Plus que réduit, le domaine des nullités s’est alors singulièrement déplacé. La question fondamentale de l’étendue de la nullité a pris le relais. Les nullités partielles, notamment des clauses léonines sous le masque trompeur des clauses réputées non écrites, ont trouvé en droit des sociétés un terrain de prédilection. Reconnaissance de la lésion comme cause de nullité (?), ce florilège de terminologies variées appelle de nouvelles analyses approfondies. En définitive, la sanction de nullité n’est plus une « arme perfide » selon le mot de THALLER, elle représente, au mieux, un « principe d’organisation » suivant la thèse de M.SIMLER ; au pire, elle demeure, pour MM. MALAURIE et AYNES, un « mal nécessaire ».
Keywords: Acte collectif; Annulabilité; Confirmation; Corporate law; Droit des sociétés; Marleasing (arrêt); Nullité; Nullité absolue; Nullité partielle; Nullité relative; Nullité textuelle; Nullité virtuelle; Ordre public sociétaire; Principe de non-rétroactivité; Responsabilité du fait de l'annulation; Régularisation